No conversion, no conversation: consequences of retail salespeople disengaging from unpromising prospects - William L. Cron; Sascha Alavi; Johannes Habel; Jan Wieseke; Hanaa Ryari (Journal of the Academy of Marketing Science, 2021)
On encountering a prospect whom they believe unlikely to make a purchase, some retail salespeople adopt a sales strategy of limiting engagement with the customer, relying on a "no conversion, no conversation" (NC2) sales strategy. Is this a good or bad sales strategy? Based on a multisource dataset combining salespeople and objective sales performance data, the authors examine retail salespeople's performance consequences of disengaging from a customer, i.e., of the NC2 sales strategy. Higher sales performance and sales growth arises from the use of an NC2 sales strategy when (1) salespeople are experienced professionals skilled in gauging customers' purchase likelihood, (2) store traffic is high, and (3) salespeople are oriented to building lasting customer relationships. However, (4) when store traffic is low and peers use the NC2 sales strategy as well, this customer disengagement strategy yields lower returns for salespeople.
Keywords: 330; Personal selling; Time allocation; Decision strategy; Intuition; Salesperson–customer relationships